2019
DOI: 10.1177/0033688219854475
|View full text |Cite
|
Sign up to set email alerts
|

Seeing What They See: Elementary EFL Students Reading Science Texts

Abstract: Science texts use various text features and multiple representations to communicate meaning to their readers. English science texts are challenging for elementary-level English as a foreign language (EFL) learners in Taiwan because they are familiar with reading language-controlled texts from textbooks. Teaching students to make use of various text features and visual representations will help them achieve a more successful science text reading experience. In this study, 27 Grade 6 Taiwanese students were inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In particular, saccades, one of the fundamental measures of eye movements, were one of the least frequently used measure indices alongside eye blinks and pupil measures in L2 studies. However, there is one positive trend showing an increase in the application of saccadic eye-movement measures (e.g., Hung et al 2020;Pellicer-Sánchez et al 2021b). This is in contrast to the findings of Godfroid (2019) who found no saccadic measures used in her sample of publications (number of papers reviewed = 84).…”
Section: Eye-tracking Measures Adoptedmentioning
confidence: 62%
See 2 more Smart Citations
“…In particular, saccades, one of the fundamental measures of eye movements, were one of the least frequently used measure indices alongside eye blinks and pupil measures in L2 studies. However, there is one positive trend showing an increase in the application of saccadic eye-movement measures (e.g., Hung et al 2020;Pellicer-Sánchez et al 2021b). This is in contrast to the findings of Godfroid (2019) who found no saccadic measures used in her sample of publications (number of papers reviewed = 84).…”
Section: Eye-tracking Measures Adoptedmentioning
confidence: 62%
“…There are some other types of gaze behaviors that have been adopted to measure attention, although less frequently, including gaze patterns (e.g., Hung et al 2020), skipping (e.g., Lee and Révész 2020), regression counts (e.g., Montero Perez 2019), and saccade spatial measures (e.g., Hung et al 2020). Gaze patterns integrate both spatial and temporal aspects of gaze behaviors, thus providing useful information to draw inferences on participants' patterns of attention (Rahal and Fiedler 2019).…”
Section: Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eye movement research has demonstrated that readers' eyes do not flow smoothly across a page of text, but rather make a series of very short pauses, called fixations, followed by extremely fast movements called saccades, to the next fixations (Hyönä & Kaakinen, 2019). Eye movements do not always proceed uniformly forward in a text, nor are the fixations always the same duration; rather, where the eyes go, and how long they stay there, are closely tied to attentional processes during reading (Hung et al., 2020). For an eye‐movement researcher, analyzing the location, order, and duration of fixations provides detailed information about a reader's comprehension processes.…”
Section: Introductionmentioning
confidence: 99%